Editorial Introduction - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2017)
At the heart of action research and teacher inquiry is a deep desire to improve one’s practice. This issue of Networks: An Online Journal for Teacher Research highlights educators at a variety of levels reflecting on their work, asking hard questions, examining data, drawing conclusions, and making improvements to their practice.